Políticas de inclusión educativa del discapacitado. barreras y facilitadores para su implementación: Bucaramanga, 2010 (2011)
ABSTRACT: To explore the factors enabling or hindering the implementation of inclusive education policies for the disabled population of Bucaramanga. Methodology: a descriptive study, involving representatives from governmental agencies (EG), members of the faculty boards of educational institutions (DIE) and guardians of disabled individuals (APSD). Physical, social, and political obstacles and facilitating factors that could potentially determine the implementation of these policies were analyzed. Data was collected through interviews. Results: there was a total of 2, 32, and 34 participants from the EG, DIE, and APSD groups respectively. Identified obstacles included: lack of strategies to support educational institutions, poor or limited teacher training, high tuition fees, and negative attitude towards disability. The facilitating factors included: availability of places, inclusion of this issue in the political agenda, and desire of the disabled individuals’ families to provide them with education. Discussion: These findings provide useful information for further research on this issue and show how action has been taken, as well as how urgent it is to establish a direct relationship between academia and the public sector to propose strategies for assessing and modifying these policies.